Fire in Mediterranean ecosystems : - Keeley, Jon E. (Cambridge University Press, 2012)
"Exploring the role of fire in each of the five Mediterranean-type climate ecosystems, this book offers a unique view of the evolution of fire-adapted traits and the role of fire in shaping Earth's ecosystems. Analyzing these geographically separate but ecologically convergent ecosystems provides key tools for understanding fire regime diversity and its role in the assembly and evolutionary convergence of ecosystems. Topics covered include regional patterns, the ecological role of wildfires, the evolution of species within those systems, and the ways in which societies have adapted to living in fire-prone environments. Outlining complex processes clearly and methodically, the discussion challenges the belief that climate and soils alone can explain the global distribution and assembly of plant communities. An ideal research tool for graduates and researchers, this study provides valuable insights into fire management and the requirements for regionally tailored approaches to fire management across the globe"-- Provided by publisher.